2012
DOI: 10.1111/j.1365-2036.2012.05131.x
|View full text |Cite
|
Sign up to set email alerts
|

Meta‐analysis: IL28B polymorphisms predict sustained viral response in HCV patients treated with pegylated interferon‐α and ribavirin

Abstract: SUMMARY BackgroundInterleukin (IL) 28B single nucleotide polymorphisms can predict sustained virological response (SVR) in hepatitis C virus (HCV) patients following pegylated interferon-alpha (PEG IFN-a) and ribavirin treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
2
4

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 84 publications
(110 reference statements)
2
37
2
4
Order By: Relevance
“…The CC genotype of rs12979860 occurred in 48.6% of patients who achieved SVR, and 47.9% of patients who were infected with HCV subtype 1b, which were significantly higher than the corresponding values of CT and TT genotypes. These findings are consistent with the results of other studies in different ethnic groups (29). Based on these findings, the rs12979860 CC genotype could constitute an effective pre-treatment predictor in Azerbaijani chronic hepatitis C patients, especially when associated with HCV subtype 1b.…”
Section: Discussionsupporting
confidence: 82%
“…The CC genotype of rs12979860 occurred in 48.6% of patients who achieved SVR, and 47.9% of patients who were infected with HCV subtype 1b, which were significantly higher than the corresponding values of CT and TT genotypes. These findings are consistent with the results of other studies in different ethnic groups (29). Based on these findings, the rs12979860 CC genotype could constitute an effective pre-treatment predictor in Azerbaijani chronic hepatitis C patients, especially when associated with HCV subtype 1b.…”
Section: Discussionsupporting
confidence: 82%
“…29 Other studies 30,31 have also demonstratedthe association of IL28B SNPs with SVR in genotype 2/3 HCV infections. However, none of these studies have exclusively examined this SNP in genotype 3 HCV patients.Besides these three studies, others have failed to show any significant association betweenIL28B polymorphisms and SVR in genotypes 2 and 3 HCV-infected patients 32 although all studies have shown an association with RVR. A recent report also shows significant association between a novelIL28B SNP (ss469415590; encoding IFN-L4) with SVR 33 in genotype 2/3 HCV infections.Therefore, the association of IL28B SNPs and SVR in genotype 2/3 HCV infections remains controversial.…”
Section: Introductionmentioning
confidence: 99%
“…HCV genotip 1 ile infekte olan hastalarda, IL28B için rs12979860 CC genotipi taşıyan hastalarda KVY oranları daha yüksektir (90). HCV genotip 2/3 ile infekte hastalarda da, HCV genotip 1 ile infekte hastalardaki kadar kesin olmamakla birlikte, ILB28 gen polimorfizmiyle KVY arasında ilişki saptanmıştır (91).…”
Section: Karaciğer Hastalığının şIddeti Ve Bazal Virolojik Göstergelerunclassified